Sistem Pakar Diagnosis Penyakit Pada Tanaman Jagung Menggunakan Metode Naive Bayes Berbasis Android - Achmad Syarifudin; Nurul Hidayat; Lutfi Fanani (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Corn crop disease is one cause of production of corn is not a maximum, downy mildew can cause harvest failures up to 90% , the presence of an expert would be helpful in terms of solving the diseases that attack plants of corn by means of identifying the symptoms that plagued and conclude what disease attack and provide information to settle the issue. Naive Bayes method is a method used to predict probabilities. While Bayes classification is the classification of statistics that can predict the probability of a class member. For a more simple Bayes classification known as naive Bayesian Classifier can be assumed that the effect of an attribute value is a class given is free of other attributes. The required variable in this study are the symptoms on the leaves, stem and cob of corn plants. The results of this research testing showed all functional requirements are valid, the accuracy of the system are 96% and the results of usability testing stated it very well.